Características fisicoquímicas del aceite esencial de Syzygium aromaticum (clavo de olor) y separación de sus componentes relativos hidrocarbonados y oxigenados - Mendez Echevarria, Maria Gracia Joselin (2019)
In this work the physicochemical characteristics of the essential oil of Syzygium aromaticum (clove) and separation of its hydrocarbon and oxygenated components were carried out. The extraction of the essential oil of Syzygium aromaticum (clove) was carried out, by means of the hydrodestilation method using the equipment clevenger in order to analyze its percentage of yield obtaining a value of 0.4%. The organoleptic characteristics that were pungent taste, suigéneris smell, transparent color and oily texture were determined. The physicochemical parameters were determined by finding a density of 1,005 and a relative density of 1.063, refractive index 1.5330, pH 5.5, the acid number 5.019, its solubility was higher in methanol, petroleum ether and lacks solubility in hexane and water. In addition, the percentage of its hydrocarbon and oxygenated components was determined, which were 70% and 28% respectively